The ability of superior student in fraction materials based on ecopreneurship - S Aryanto; E Syaodih; B Maftuh; A Jagad (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
One of the innovations in mathematics learning is the implementation of ecopreneurship principle as a representation of social science approaches in developing fractional problems at the inclusive of primary school aimed at superior students. So this study aims to provide an overview of superior students understanding skills in fractional materials through the development of questions based ecopreneurship that are expected to improve superior students cognitive ability and be able to interpret questions that implicitly imply the principle of ecopreneurship. This Action Research conducted on 3 superior students in the inclusive of primary school proves that there is an enhancement in students understanding in fractional material in cycle II by 45% when it compared with cycles I. the indicators is that students are able to apply the concepts and answer the questions precisely in addition to implicitly they are able to understand the content of questions related to the principle of ecopreneurship. The results are expected to become the reference for the teachers in developing more innovative mathematics lessons. This concept is expected to be a new finding that is useful in improving superior students understanding in answering mathematical fractions and is expected to be able to train their social skills.